2004
DOI: 10.1002/ajh.20182
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan induces apoptosis of human HS-Sultan cells accompanied by activation of caspase-3 and down-regulation of ERK Pathways

Abstract: Fucoidan, a sulfated polysaccharide in brown seaweed, was found to inhibit proliferation and induce apoptosis in human lymphoma HS-Sultan cell lines. Fucoidan-induced apoptosis was accompanied by the activation of caspase-3 and was partially prevented by pretreatment with a pan-caspase inhibitor, Z-VAD-FMK. The mitochondrial potential in HS-Sultan cells was decreased 24 hr after treatment with fucoidan, indicating that fucoidan induced apoptosis through a mitochondrial pathway. When HS-Sultan was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
218
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(233 citation statements)
references
References 30 publications
7
218
2
6
Order By: Relevance
“…Although the exact cytotoxic mechanisms of these sulfated polysaccharides are still unclear, it has been reported that fucoidan was able to induce apoptotic cell death in the human lymphoma HS-Sultan cell line through the activation of caspase-3 (20). Our recent study has demonstrated that ascophyllan also induces apoptosis in U937 cells, as judged by typical apoptotic nuclear morphological changes and DNA fragmentation (14).…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact cytotoxic mechanisms of these sulfated polysaccharides are still unclear, it has been reported that fucoidan was able to induce apoptotic cell death in the human lymphoma HS-Sultan cell line through the activation of caspase-3 (20). Our recent study has demonstrated that ascophyllan also induces apoptosis in U937 cells, as judged by typical apoptotic nuclear morphological changes and DNA fragmentation (14).…”
Section: Resultsmentioning
confidence: 99%
“…A number of genes that are associated with apoptotic cell death were tested in order to clarify the mechanism by which fucoidan treatment induces apoptosis in MDA-MB-231 cells. According to some previously conducted studies, caspases act as key players of fucoidan-induced apoptosis [20][21][22][23][24][25][26][27] . These findings have guided the researcher to propose a model in which fucoidan promotes apoptosis in MDA-MB-231 cells through increasing caspases activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has demonstrated that a commercially available fucoidan (Sigma, St. Louis, MO) purified from Fucus vesiculosus induced apoptosis in human myeloma and leukemia cells through activation of the caspase-3 and down-regulation of ERK pathways. 16) In addition, Riou et al reported that fucoidan extract obtained from Ascophyllum nodosum directly inhibited the proliferation of a human non-small cell lung cancer cell line (NSLC-N6). 17) Thus, it seems likely that sulfated fucans like fucoidans and ascophyllan are able to cause direct cytotoxic effects on target cells, including tumor cells, through induction of apoptosis.…”
mentioning
confidence: 99%